Role of bacillus Calmette-Guerin as an immunomodulator for the prevention and treatment of allergy and asthma - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2005)
Purpose of review As an essential part of the hygiene hypothesis, the association between exposure to mycobacterial components and the prevention, development and severity of atopic diseases has not been fully understood. The current status on the causal-effect link of this relationship and the potential use of mycobacterial adjuvants as a preventive or disease-modifying modality in allergic diseases is reviewed in this article. Recent findings Data obtained from human and animal models indicate a discrepancy regarding the preventive and therapeutic effect of bacillus Calmette-Guerin in atopic diseases. Among the issues that require clarification include whether the distinction in T helper type 1/2 cells decribed in mice can be fully extrapolated to humans. Other factors involved could be caused by genetic variation, optimal timing, dose, route of delivery as well as environmental factors, which affect the degree of natural exposure to pathogenic or saprophytic mycobacteria. Summary Most of the evidence available to date suggests a need for an improved mycobacterial vaccine administered early in life, by means of alternative routes, preferentially mucosal. As switching away from the T helper type 2 immune response by inducing T helper type 1 is unable to explain the underlying mechanisms of action of mycobacterial antigens, it may be worthwhile to investigate whether T regulatory cells are induced in response to different mycobacterial adjuvants.
Keywords: allergy; asthma; atopy; bacillus Calmette-Guerin; IgE; mycobacteria; T cells; toll-like receptors; KILLED MYCOBACTERIUM-VACCAE; BCG VACCINATION; AIRWAY HYPERRESPONSIVENESS; TUBERCULIN REACTIVITY; IGE PRODUCTION; T-CELLS; IMMUNE-RESPONSES; IMMUNOGLOBULIN-E; ATOPIC DISORDER; GUINEA-BISSAU